90 Role of microrna-145 in epithelial ovarian cancer. (4th December 2020) - Romero, Carmen; Garrido, Maritza P; Torres, Ignacio; Hernandez, Andrea; Chnaiderman, Jonas; Vega, Margarita; Selman, Alberto; Preisler, Jessica; Lobos, Lorena
Abstract : Introduction/Background: Epithelial ovarian cancer (EOC) is one of the deadliest gynaecologic malignancies worldwide. Nerve Growth Factor (NGF) and its high affinity receptor TRKA increase during epithelial ovarian cancer progression, promoting cell proliferation and angiogenesis, by increasing several oncogenic proteins. Many reports have showed that microRNA-145 (miR-145) is down-regulated in EOC, promoting the increase of oncoproteins. Our aims of were to evaluate whether NGF changes the miR-145 levels in EOC cells and the role of this miR in vitro and in vivo experiments. Methodology: The human tissues and blood samples were obtained with informed consent and approved by Ethic Committee of our Institution. MicroRNA-145 levels were measured by qPCR in EOC samples, EOC cells lines (A2780 and SKOV3) and in serum samples. NGF action on miR-145 levels in EOC cell lines were evaluated using an inhibitor of TRKA (high affinity receptor of NGF). The over-expression of miR-145 in EOC cells were done by lipofectamine 2000 and by pGPGLenti-CMV-GFP vector. As control we also used the empty vector. After the transfection assay it was evaluated the migration and invasion of A2780 and SKOV3 cells. After stable miR over-expression assays, the GFP-expressing cells were sorted using GFP mark and the in vivo assays were done. Animal studies were conducted in accordance with appropriate guidelines of Ethical Committee of the Institution. Two groups of Immune-compromised NOD/SCID mice were injected with 8 x106 cells (intraperitoneal and subcutaneous) of A2780 or SKOV3 cells. Results: NGF decreased the miR-145 levels in A2780 and SKOV3 cell lines. Also, when an inhibitor of TRKA receptor was used, levels of this miR increased. Beside, miR-145 levels decreased with the EOC progression in both tissues and plasma samples. MicroRNA-145 over-expression in EOC cells decreased cell proliferation and invasion. Also, the stable over-expression of miR-145 in EOC cells lines decreased malignant ascites presence in the animals. On the other hand, a delay in the tumour formation was observed in EOC cells which over-express miR 145 in subcutaneous lateral flank compared with the mice injected with control EOC cells. Conclusion: These results suggest that overexpression/delivery of miR-145 could be a future adjuvant therapy in epithelial ovarian cancer Disclosures: The authors declare that there is no conflict of interest. This work was funded by Fondo Nacional de Desarrollo Científico y Tecnológico (FONDECYT) N° 1160139 to CR